The Paradox of Yuri Lotman’s Cultural Semiotics - Cibarauskė, Virginija (Colloquia, 2016)
The author of this article discusses the reception, in recent decades, of Yuri Lotman’s cultural semiotics and the project of cultural semiotics itself. She pays particular attention to the idea of the interplay between textual and non-textual structures, which is crucial to cultural semiotics. Although Lotman has been very widely cited in studies by Lithuanian humanities scholars since the sixties, only a few articles have critically reflected on his project of cultural semiotics. Lotman is usually presented as a structuralist interested in “secondary modeling systems” and his semiotic theory is compared to that of Algirdas Julius Greimas or some other theory, such as New Historicism. At the same time, outside of Lithuanian academic circles more attention is paid to Lotman’s later works, stressing the connections between cultural semiotics and literary sociology and anthropology. A reconstruction of Lotman’s concepts – such as interplay, world model, and modeling – reveals that the object of Lotman’s cultural semiotics is not immanent secondary modeling systems but the interplay between texts and different cultural languages, structures that are always within a specific context. Lotman is especially interested in shifts of meaning that occur when text and context, text and reader interact. In this sense, Lotman’s semiotics inserts itself between traditional semiotics and literary/cultural sociology, reception theory, anthropology, and literary history – theories and disciplines which not only influenced Lotman’s theory but were themselves significantly affected by it.